2001
DOI: 10.1007/s002130000625
|View full text |Cite
|
Sign up to set email alerts
|

St. John's wort (Hypericum perforatum): a review of the current pharmacological, toxicological, and clinical literature

Abstract: Additional research on the pharmacological and biochemical activity of Hypericum and its several bioactive constituents is necessary to further elucidate the mode(s) of antidepressant action. Given what is currently known and unknown about the biological properties of Hypericum, those who choose to use this herb should be closely monitored by a physician.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
219
0
19

Year Published

2002
2002
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 328 publications
(239 citation statements)
references
References 85 publications
1
219
0
19
Order By: Relevance
“…Hypericum perforatum (St. John's Wort) is an increasingly popular alternative to conventional medications used for the treatment of mild to moderate depression [1][2][3]. Aggressive analysis of this plant over the last three decades has revealed that it possesses several biological properties, including antidepressant, antiviral and antiproliferative activities [4][5][6][7][8].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Hypericum perforatum (St. John's Wort) is an increasingly popular alternative to conventional medications used for the treatment of mild to moderate depression [1][2][3]. Aggressive analysis of this plant over the last three decades has revealed that it possesses several biological properties, including antidepressant, antiviral and antiproliferative activities [4][5][6][7][8].…”
Section: Introductionmentioning
confidence: 99%
“…Although H. perforatum (Hp) is most commonly used as an alternative to standard tricyclic antidepressants, other biological properties possessed by this plant have also been utilized for the treatment of cancer and viral infections [8][9][10][11][12]. Widespread use of Hp as an alternative medicine has raised concern regarding its safe use by the public [1,2]. In order to better understand the efficacy and safety of Hp herbal preparations, it has become imperative to identify and characterize the biologically active constituents composing this plant species and determine if agents in Hp are able to prevent the toxicity of key constituents such as hypericin.…”
Section: Introductionmentioning
confidence: 99%
“…In fact, the active constituents are not fully known. The pharmacological activity of SJW extracts has recently been reviewed (Butterweck, 2003;Greeson et al, 2001;Nathan, 1999). Reports about the antidepressant activity of SJW extracts and their constituents both in vivo and in vitro have been published (Baureithel et al, 1997;Butterweck et al, 1997Butterweck et al, , 1998Butterweck et al, , 2000Butterweck et al, , 2001aButterweck et al, , b, 2002Calapai et al, 1999;Chatterjee et al, 1996Chatterjee et al, , 1998aDi Matteo et al, 2000;Franklin and Cowen, 2001;Gobbi et al, 1999Gobbi et al, , 2001Müller et al, 1997Müller et al, , 1998Müller et al, , 2001Simmen et al, 1999Simmen et al, , 2001Singer et al, 1999;Wonnemann et al, 2001).…”
Section: Introductionmentioning
confidence: 99%
“…John's wort (Hypericum perforatum L.) (SJW) is a widely distributed herbaceous perennial plant, well-known as a medicinal plant since antiquity for a variety of ailments such as diuretics, in neuralgic conditions, in sciatica and in reptile bites [1], in inflammations of the bronchi and urogenital tract, treatment of biliary disorders, bladder irritation, cold, diabetes mellitus, migraine headaches and ulcer [2]. Herbal medicinal products (HMPs) based on hydroalcoholic extracts and standardized, using the naphthodianthrones of the hypericin group, calculated as 0.2 -1 mg of hypericin as a daily dose are prescribed in Europe for the treatment of mild to moderate depressions [3,4], particularly in Germany where it is approximately 20 times more often prescribed than fluoxetine [5]. However, in both Europe and the USA, SJW preparations are also marketed as dietary supplements [4].…”
Section: Introductionmentioning
confidence: 99%
“…However, in both Europe and the USA, SJW preparations are also marketed as dietary supplements [4]. The plant contains a great variety of secondary metabolites belonging to the groups of terpenes (0.1 -0.25% of volatile oils), flavonoids (2.0 -4.0% of quercetin glycosides), biflavonoids (I3, IIb-biapigenin up to 0.5%), naphthodianthrones (0.05 -0.3% of which 80 -90% are hypericin and pseudohypericin), phloroglucinols (up to 4.5% hyperforin and 1.8% adhyperforin), oligomeric proanthocyanidins, phenylpropanoids (mainly chlorogenic acid) and traces of xanthones and anthraquinones [3,5,6]. Among the characteristic constituents of H. perforatum are the naphthodianthrones, mainly represented by hypericin and pseudohypericin which have been the focus of extensive scientific research as important antiviral agents against a variety of viruses (herpes, murine cytomegalovirus, sindbis, hepatitis B, equine anemia, including the human immunodeficiency virus (HIV) [7].…”
Section: Introductionmentioning
confidence: 99%